The Implementation of Translation Ideology of Cultural Terms in Andrea Hirata’s Novel Laskar Pelangi - Pahlawanita, Nur Via; Hartono, Rudi; Faridi, Abdurrachman (Universitas Negeri Semarang, 2019)
This research is concerned with translation study, which is the translation ideology used in the translation of cultural terms found in Andrea Hirata’s novel LaskarPelangi into its English version, The Rainbow Troops. The objectives of the research are to answer the following four things : (1) to describe the cultural terms items categories found in the novel (2) to describe the techniques of translation applied in the translation of term items found in the novel to its translation (3) to describe the ideology of translation applied, in the translation of cultural term items found in the novel and its translation, and (4) to describe the degree of meaning equivalence of the Indonesian cultural terms in the novel as realized in its translation. The writer uses qualitative descriptive method in order to reach the objective of the research. The writer employs himself to collect data; by reading the novel and its translation, marking the cultural words, classifying, selecting and analyzing them based on the theories of translation procedure and translation strategy which are taken from some relevant references. The findings of this research show that: first, there were 168 data of cultural terms found in the novel, and categorized into Newmark’s five categories of cultural terms, with the following results : ecology category 48 data, material culture 27 data, social culture 14 data, social organization 77 data, and gesture and habit 2 data; second, the are 12 translation techniques applied by the translator, third, based on the techniques of translation used, that mostly tend to Target Language, it can be concluded that the translation ideology used by the translator is domestication ideology; fourth, the degree of meaning equivalence were 60.12 % fully equivalence, 31.55 % partly equivalence, 5.95 %non-equivalence, and 2.38% unrealized.